Towards a Typology of Learning Workers: Latent Class Analysis of Adult Education Participation in the United States - Chang Sung Jang; Doo Hun Lim; Sumi Lee (Adult Education Research Conference, 2023)
This study identifies a typology of learning workers by investigating profiles of individuals participating in adult education. Using latent class analysis, we examined four classes and their associations with covariates.
Keywords: learning workers; adult education participation; latent class analysis; PIAAC